2015
DOI: 10.1109/mei.2015.7126073
|View full text |Cite
|
Sign up to set email alerts
|

Nanodielectrics: opportunities and challenges

Abstract: This article highlights recent findings and issues concerning nanodielectric research and outlines possible future work on nanodielectrics, in particular in relation to nanofiller/ polymer interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 72 publications
0
56
0
Order By: Relevance
“…Nevertheless, many nanodielectric investigations in the first 10 years neither confirmed nor observed the enhancement of dielectric strength in thermoset plastic‐based nanocomposites. [ 97–102 ] Notably, minimal results reported encouragement in filled thermoplastic thin films. These studies clearly showed that only performing organic functionalization on nanofillers has a minimal role.…”
Section: Endeavors To Enhance Dielectric Strengthmentioning
confidence: 99%
“…Nevertheless, many nanodielectric investigations in the first 10 years neither confirmed nor observed the enhancement of dielectric strength in thermoset plastic‐based nanocomposites. [ 97–102 ] Notably, minimal results reported encouragement in filled thermoplastic thin films. These studies clearly showed that only performing organic functionalization on nanofillers has a minimal role.…”
Section: Endeavors To Enhance Dielectric Strengthmentioning
confidence: 99%
“…Chemical treatment also involve extra additives that help to separate the fillers. This includes the use of surfactants, which help to reduce high surface energy and interfacial tension in nanofillers . Improvement in dielectric properties such as AC and DC breakdown strength , electrical and water tree resistance as well as reduction in the space charge , partial discharge , permittivity and dielectric loss has been widely documented in nanocomposites with chemically treated nanoparticles.…”
Section: Application Of Micro and Nano‐size Filler In High Voltage Inmentioning
confidence: 99%
“…Indeed, thanks to the presence of the nanofiller/polymer interfaces [5][6][7][8][9], such material systems have been envisioned as an answer to many high voltage insulation problems [10]. For example, the partial discharge resistance, electrical treeing growth, space charge formation and dielectric breakdown performance of nanodielectrics have been compared with the respective unfilled and microfilled counterparts and worthwhile improvements in such properties have been reported [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%